FE-RICH CORDIERITES FROM ACID VOLCANIC ROCKS, AN OPTICAL AND X-RAY SINGLE-CRYSTAL STRUCTURE STUDY - Armbruster T. (My University, 1985)
Low-cordierites from volcanic rocks of Tuscany (Italy), Lipari (Italy), and of the Cerberean Cauldron (Australia) were investigated. Both single crystal structure refinements and optical data indicate that the Italian samples contain only low concentrations of volatiles (<0.3 wt.%), whereas in the crystals from the Cerberean Cauldron more than 50% of the structural channels are occupied, preferentially by H2O (1.6–1.9 wt.%). This high volatile concentration is in qualitative agreement with the estimated p,T-conditions (4–4.5 kbar at 750–780° C) of the magma prior to eruption. In contrast, the Italian cordierites have formed at temperatures above 950° C and pressures below 2 kbars. Low-cordierites of volcanic origin reveal the same high degree of Si, Al-ordering as observed for low-cordierites from metamorphic rocks and pegmatites. The crystals studied possess F(mol)=(Fe+Mn)/(Fe+Mn+Mg)>0.4 and provide additional information about the crystal structure of Fe-rich cordierites. With increasing Fe→Mg substitution the mean T11(Al)-O distance decreases slightly, which is probably not caused by substitution of smaller cations on t11 but by angular distortion of the tetrahedron.